RANCANG BANGUN PERTANIAN STROBERI BERBASIS INTERNET OF THINGS - Leo Puja Artana, I Komang; Wiharta, Dewa Made; Linawati, Linawati (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p1, 2020)
Technological developments have been utilized in various fields of science, including agriculture. Technology support in agriculture has been proven to be able to provide better production results. In this study, an IoT-based agricultural environmental monitoring system was developed. The system was built using Raspberry Pi as a microcontroller and data processing center, equipped with a moisture sensor and a DHT 11 temperature sensor. This system was applied to a laboratory-scale strawberry farm. The system works automatically to regulate the temperature and humidity of the plant environment. If the temperature and humidity of the strawberry plants do not meet the standards, the pump will automatically water to keep the strawberry plants at the appropriate temperature and humidity. The system is also equipped with a notification feature so that strawberry farmers can obtain information through telegram media when the temperature of the strawberry plants is hot and the soil of the strawberry plants is dry. This tool is also equipped with a webcam camera as an additional feature that serves to detect the level of ripeness of the strawberries in terms of the color of the fruit. The camera will detect the color of the strawberry, and if the strawberry is red, the strawberry is categorized as ripe, and the farmer will get a notification via telegram in the form of a picture that the strawberry is ready to be harvested.